Clinical experience with trans-catheter aortic valve implantation at a tertiary hospital in the Republic of Ireland - Tanner, Richard; Moran, Barbara; Margey, Ronan; Blake, Gavin; McGorrian, Catherine; Geraghty, Jacqueline; Groarke, Susan; Boleckova, Jana; Hurley, John; Roy, Andrew; Barton, David; Sugrue, Declan; et al. (Irish journal of medical science, 2020)
INTRODUCTION: There is a paucity of published data on the clinical experience with trans-catheter aortic valve implantation (TAVI) in the Republic of Ireland. We sought to examine the clinical outcomes of patients with medium-term follow-up treated with TAVI at our institution. METHODS: A prospective TAVI registry was used to assess the baseline demographics, procedural variables and clinical outcomes of patients treated with TAVI between the inception of the programme in 2008 and November 2017. RESULTS: A total of 354 patients (mean age 80.9 ± 8.1 years, 58% male, mean STS score 6.1 ± 4.3%) were treated during the study period. Major in-hospital outcomes included in-lab death (n = 2, 0.6%), stroke (n = 8, 2.2%), device embolisation (n = 4, 1.2%), permanent pacemaker implantation (n = 22, 6.2%) and major vascular complication (n = 2, 0.6%). The median length of hospital stay was 4 days (IQR 2-8 days). The Kaplan-Meier estimate of freedom from death at 30 days and 1 year for the entire cohort was 97 ± 1% and 85.4 ± 2.3%, respectively. Trans-femoral access was associated with a significantly lower rate of death and/or stroke at 1 year compared to trans-apical access (84.9 ± 2.4% versus 60 ± 8.9%, p = 0.0005). There was no significant difference in freedom from death and/or stroke at 1 year between balloon-expandable and self-expanding valves (81.6 ± 2.6% versus 84.4 ± 7.4%, p = 0.63). CONCLUSION: This study documents low complication rates and favourable rates of survival following TAVI in a consecutive series of patients undergoing TAVI at a tertiary referral centre in the Republic of Ireland. These data support the application of this therapy in the Irish context.
Keywords: Ireland; cévní mozková příhoda; Aortic Valve Stenosis; Clinical outcomes; Prospective Studies; senioři nad 80 let; Humans; Aortic Valve; prospektivní studie; Aged, 80 and over; Cohort Studies; centra terciární péče; Transcatheter Aortic Valve Replacement; Kaplanův-Meierův odhad; transkatetrální implantace aortální chlopně; Registries; mužské pohlaví; Stroke; Tertiary Care Centers; Aortic stenosis; aortální chlopeň; výsledek terapie; Treatment Outcome; registrace; aortální stenóza; Irsko; ženské pohlaví; TAVI; lidé; kohortové studie; Aged; senioři; Male; Trans-catheter aortic valve replacement; Kaplan-Meier Estimate; Female